Endoplasmic Reticulum Lumenal Indicators in Drosophila Reveal Effects of HSP-Related Mutations on Endoplasmic Reticulum Calcium Dynamics - Oliva, Megan K.; Pérez-Moreno, Juan José; O’Shaughnessy, Jillian; Wardill, Trevor J.; O’Kane, Cahir J. (Frontiers in Neuroscience, 2020)
Genes for ER-shaping proteins are among the most commonly mutated in Hereditary Spastic Paraplegia (HSP). Mutation of these genes in model organisms can lead to disruption of the ER network. To investigate how the physiological roles of the ER might be affected by such disruption, we developed tools to interrogate its Ca2+ signaling function. We generated GAL4-driven Ca2+ sensors targeted to the ER lumen, to record ER Ca2+ fluxes in identified Drosophila neurons. Using GAL4 lines specific for Type Ib or Type Is larval motor neurons, we compared the responses of different lumenal indicators to electrical stimulation, in axons and presynaptic terminals. The most effective sensor, ER-GCaMP6-210, had a Ca2+ affinity close to the expected ER lumenal concentration. Repetitive nerve stimulation generally showed a transient increase of lumenal Ca2+ in both the axon and presynaptic terminals. Mutants lacking neuronal reticulon and REEP proteins, homologs of human HSP proteins, showed a larger ER lumenal evoked response compared to wild type; we propose mechanisms by which this phenotype could lead to neuronal dysfunction or degeneration. Our lines are useful additions to a Drosophila Ca2+ imaging toolkit, to explore the physiological roles of ER, and its pathophysiological roles in HSP and in axon degeneration more broadly.